Simulasi Pembagian Batang Sistem Kayu Pendek pada Penebangan Pembagian Batang Kayu Serat Jenis Mangium (Simulation of Shortwood Bucking System on Bucking Pulpwood of Mangium) - Budiaman, Ahmad; Prabowo, Rendy Heryandi (Jurnal Manajemen Hutan Tropika, 2011)
This paper presented results of simulation of shortwood bucking system on bucking pulpwood of mangium (Acacia mangium) at an industrial plantation forest in South Kalimantan. A set of logs bucking policy of short wood system, which was applied in the state owned company (Perum Perhutani), was used in the bucking simulation, which divided logs into large logs assortment (KBB), medium logs assortment (KBS), and small logs assortment (KBK). The KBB represented veneerlogs, KBS represented sawlogs, whereas KBK represented pulplogs. The result of the study indicated that application of bucking in varieties wood assortments resulted in a potential number of high quality logs of mangium. The results of the proposed logs bucking were 22% large logs, 54% medium logs and 24% small logs. In the other side, application of pulpwood bucking policy only resulted to 4.7% large logs, 64.2% medium logs and 23.3% small logs.